A plateau-valley separation approach (PVSA) for reduction of the end-effect in surface metrology. (December 2021) - Podulka, Przemysław
Abstract: In this paper the novel method for analysis of the results of surface topography measurement was presented. The plateau-valley separation approach (PVSA), based on the thresholding of the valley component of the analysed surface texture detail was proposed. Cylindrical topographies with additionally burnished dimples and laser-textured surfaces, measured with a stylus or optical instruments were studied. It was found that the PVSA method can be fairly advantageous in areal surface texture analysis than regular, commonly-used procedures. The effect of the PVSA scheme on values of areal surface topography parameters, from ISO 25178 standards, were also studied in detail.